Abstinence and marginality - Borgeaud, Philippe (ARYS. Antigüedad: Religiones y Sociedades, 2024)
This essay addresses the question of abstinence from meat, which implies the renunciation of animal sacrifices organised at the expense of the city. Does this abstinence constitute a kind of heresy, from an ancient Greek perspective ultimately comparable to the modern point of view?